Sport as medicine: How F3 is building healthier men and communities - Warner, Stacy (My University, 2019)
Given sport has been largely absent from U.S. public health policies and discourse, the author suggests ways that sport can be better managed to promote health. Using a critical perspective and grounded theory approach, the author examined the experiences of 14 men in the grassroots recreational program, F3. Data were collected through observation and semi-structured interviews. Based on the results, a conceptual model that suggests how sport should be managed to address illnesses related to physical inactivity is put forth. The resulting Sport as Medicine model indicates that Creating a Team Structure, Providing a Place to Be Accountable, and Ensuring No One is Left Out, led to meaningful Health Outcomes, including Physical Health, Mental Toughness, and Social Connections. As the distinctiveness of sport continues to emerge, the author provides a framework to consider how sport can be part of public health efforts to address physical inactivity. Thus, this work positions sport as medicine by pinpointing how sport can be managed so that holistic health outcomes are more likely achieved.
Keywords: Sport management theory; Public health; Physical activity; Community sport